“A Triple-Frame Model of Genre: Framing for Discourse Sequencing.” - Sinding, Michael (Genre in Language, Discourse and Cognition, 2016)
I propose a theoretical model of genre with parameters organized in terms of the concept of “frame.” The model has three nested frames: a sociocognitive action frame contains a rhetorical situation frame, which contains a discourse structure frame. I motivate the model in relation to existing research on both literary and extraliterary genres, sketch its advantages and the lines of research it suggests, then address challenges to it. First, to clarify how genre relates to language, discourse and cognition, and my investments in various research areas, I review major conundrums about genre identity. Second, I argue for an inclusive approach to genres, as against defining “genre” to suit assumptions and methods. Third, I discuss the broader conception of discourse structure and sequencing that this inclusive approach entails. Fourth, I investigate frame-based sequencing in text composition—specifically, how poets adapt everyday genre frames for literary purposes. I propose a theoretical model of genre with parameters organized in terms of the concept of “frame.” The model has three nested frames: a sociocognitive action frame contains a rhetorical situation frame, which contains a discourse structure frame. I motivate the model in relation to existing research on both literary and extraliterary genres, sketch its advantages and the lines of research it suggests, then address challenges to it. First, to clarify how genre relates to language, discourse and cognition, and my investments in various research areas, I review major conundrums about genre identity. Second, I argue for an inclusive approach to genres, as against defining “genre” to suit assumptions and methods. Third, I discuss the broader conception of discourse structure and sequencing that this inclusive approach entails. Fourth, I investigate frame-based sequencing in text composition—specifically, how poets adapt everyday genre frames for literary purposes.
Keywords: genre; cognition; frame; sociocognitive action; rhetorical situation; discourse structure